2004
DOI: 10.1200/jco.2004.05.114
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of the Humanized Antiepidermal Growth Factor Receptor Monoclonal Antibody EMD72000 in Patients With Advanced Solid Tumors That Express the Epidermal Growth Factor Receptor

Abstract: Treatment with EMD72000 was well tolerated and showed evidence of activity in heavily pretreated patients with EGFR-expressing tumors. EMD72000 at the investigated doses significantly inhibited downstream EGFR-dependent processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
104
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(111 citation statements)
references
References 31 publications
6
104
1
Order By: Relevance
“…Cutaneous toxicities, commonly defined as rash, acne, pruritus and dry skin, have been reported as one of the predominant side effects in cancer patients treated with small-molecule tyrosine kinase inhibitors (TKI) of EGFR (gefitinib, erlotinib), dual EGFR/HER2 (lapatinib) inhibitors, pan-HER (CI-1033) inhibitors and anti-EGFR antibodies (cetuximab, ABX-EGF and EMD72000) (Busam et al, 2001;Hidalgo et al, 2001;Shin et al, 2001;Fukuoka et al, 2003;Kris et al, 2003;Burris, 2004;Rowinsky et al, 2004;Vanhoefer et al, 2004).…”
mentioning
confidence: 99%
“…Cutaneous toxicities, commonly defined as rash, acne, pruritus and dry skin, have been reported as one of the predominant side effects in cancer patients treated with small-molecule tyrosine kinase inhibitors (TKI) of EGFR (gefitinib, erlotinib), dual EGFR/HER2 (lapatinib) inhibitors, pan-HER (CI-1033) inhibitors and anti-EGFR antibodies (cetuximab, ABX-EGF and EMD72000) (Busam et al, 2001;Hidalgo et al, 2001;Shin et al, 2001;Fukuoka et al, 2003;Kris et al, 2003;Burris, 2004;Rowinsky et al, 2004;Vanhoefer et al, 2004).…”
mentioning
confidence: 99%
“…Matuzumab was administered to three patients in each dose group in an escalating, sequential manner in combination with a fixed dose of gemcitabine (1000 mg m -2 once weekly for 3 weeks, followed by a 1-week rest). Three matuzumab dose levels were planned on the basis of the prior studies (Vanhoefer et al, 2004): group I, 400 mg once weekly; group II, 800 mg every 2 weeks; and group III, 800 mg once weekly. If a DLT was observed in one of the three patients at one dose level, an additional three patients were enrolled at this dose level.…”
Section: Study Design and Treatmentmentioning
confidence: 99%
“…A phase I clinical trial with matuzumab demonstrated that it is well tolerated as a single agent at doses between 400 and 1600 mg administered weekly, biweekly, or every 3 weeks (Vanhoefer et al, 2004). Dose-limiting toxicities (DLTs) occurred at 2000 mg on a weekly schedule and consisted of grade 3 headache and fever.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Normal tissue-based PD approaches have already been used with success during the clinical development of anticancer drugs acting on biomarkers present within peripheral blood mononuclear cells (Cohen et al, 2003;Peralba et al, 2003), exfoliated buccal squames (van de Vaart et al, 2000;Adjei et al, 2003) and punch biopsies of the skin (Albanell et al, 2002;Malik et al, 2003;Vanhoefer et al, 2004). The choice of normal tissue for a given drug study is likely to depend on a number of different factors, including the level and variability of expression of the biomarker of interest.…”
mentioning
confidence: 99%